The subgenus Monilearia (Lyrula) Wollaston, 1878 (Gastropoda: Helicoidea: Cochlicellidae) from Lanzarote and Fuerteventura (Canary Islands), with the description of Monilearia (Lyrula) tubaeformis sp. nov. - Ibáñez, Miguel; Groh, Klaus; Alonso, María R.; Castillo, Carolina; Yanes, Yurena (Zootaxa, 2006)
Monilearia tubaeformis sp. nov. is described from Fuerteventura (Canary Islands) and placed in the taxon Lyrula Wollaston, 1878, previously considered as monospecific, for its distinctive type of shell ornamentation. Helix multipunctata Mousson, 1872, from the same island, is also placed in Lyrula because it has similar shell ornamentation. The anatomy of the genital system of both species shows that Lyrula should be treated as a subgenus of Monilearia Mousson, 1872. A new diagnosis of Monilearia (Lyrula) is added